2023
DOI: 10.1136/bmjopen-2022-070907
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of breast cancer-related lymphoedema: protocol of an umbrella review

Abstract: IntroductionBreast cancer-related lymphoedema (BCRL) is a progressive and debilitating complication post-breast cancer treatment. Identifying potential risk factors facilitates the prevention and management of BCRL. Multiple systematic reviews have been conducted to address the variables correlated with the occurrence of BCRL. This study aims to identify and examine factors predicting the development of BCRL, to clarify the predicting mechanism of these factors, as well to determine the credibility of risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, this umbrella review also suffers from a common limitation observed in most umbrella reviews, 40–42 wherein new and recent individual articles may not be included if they have not been incorporated into published systematic reviews and meta‐analyses. This restriction can result in the omission of potentially relevant studies that have emerged since the publication of the included reviews, thus limiting the comprehensiveness and currency of the synthesized evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this umbrella review also suffers from a common limitation observed in most umbrella reviews, 40–42 wherein new and recent individual articles may not be included if they have not been incorporated into published systematic reviews and meta‐analyses. This restriction can result in the omission of potentially relevant studies that have emerged since the publication of the included reviews, thus limiting the comprehensiveness and currency of the synthesized evidence.…”
Section: Discussionmentioning
confidence: 99%
“…), ultimately impacting work capacity and overall quality of life. [3][4][5][6] The current treatment options for the BCRL include complete decongestive therapy (CDT) [7] (including bandaging, compression garments, and manual lymphatic drainage), pneumatic compression, low-level laser therapy, physical exercise, acupuncture, surgery, etc. [1] Most clinicians base their decision to recommend the treatment options on patients' objective measurement of lymphedema, ignoring their self-reported symptoms.…”
Section: Introductionmentioning
confidence: 99%